2008
DOI: 10.1111/j.1939-1676.2008.0097.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Ultrasound Methods for Quantifying Left Ventricular Systolic Function: Correlation with Disease Severity and Prognostic Value in Dogs with Mitral Valve Disease

Abstract: Background: End-systolic volume index (ESVI) is a marker of systolic function, which can be assessed by the geometric (GM, based on Teichholz formula) or 2 planimetric methods (PM, Simpson's derived and length area methods).Hypothesis: Systolic dysfunction (SyD) may be observed in dogs with mitral valve disease (MVD) and is better assessed by PM than GM, which does not take into account the longitudinal left ventricular systolic shortening.Animals: Six healthy dogs were used to determine the variability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
84
5
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 31 publications
8
84
5
5
Order By: Relevance
“…This would indicate, as previously suggested,11 that either ESVI is higher in these 3 breeds compared with other breeds, suggesting intrinsic systolic dysfunction, or the cut‐off value of 30 mL/m² is too low. In contradiction to this study, the range of SMOD‐derived ESVI was below the cut‐off of 30 mL/m² (9.5–25.4 mL/m²) in a previous study including a group of 24 healthy smaller breed dogs (<10 kg) 19. Because of the large overlap between normal and abnormal values in the ESVC guidelines and several studies describing ESVI >30 mL/m²,11, 12 further study in dogs of different breeds is warranted to determine SMOD‐derived ESVI cut‐offs.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This would indicate, as previously suggested,11 that either ESVI is higher in these 3 breeds compared with other breeds, suggesting intrinsic systolic dysfunction, or the cut‐off value of 30 mL/m² is too low. In contradiction to this study, the range of SMOD‐derived ESVI was below the cut‐off of 30 mL/m² (9.5–25.4 mL/m²) in a previous study including a group of 24 healthy smaller breed dogs (<10 kg) 19. Because of the large overlap between normal and abnormal values in the ESVC guidelines and several studies describing ESVI >30 mL/m²,11, 12 further study in dogs of different breeds is warranted to determine SMOD‐derived ESVI cut‐offs.…”
Section: Discussioncontrasting
confidence: 99%
“…An interesting and unexpected finding in this study was that in healthy Boxer dogs, the volumes calculated by Teichholz measurements and the volumes derived by SMOD were quite comparable. This is in contrast to findings by Tidholm and Serres, which showed that Teichholz measurements overestimated the volumes by a factor of 2 10, 19. Differences between the Teichholz and SMOD estimations of LV volume may be more pronounced in disease states than in healthy dogs 8.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Cardiac output (CO) and the ejection fraction (EF) were calculated using the modified Simpson method, as described byBOON (2011). Fractional shortening (FS) was calculated from left ventricular diameter values obtained during diastole and systole, as described by SERRES (2008).…”
Section: Methodsmentioning
confidence: 99%